2013
DOI: 10.5812/ircmj.5364
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Malignant Melanoma in Central Iran: A 20-Year Study

Abstract: BackgroundSkin cancers are the most common cancers around the world. Cutaneous malignant melanoma (CMM) is the malignancy of melanocytes that are mainly located in the skin and mucous membranes.ObjectiveThis study tried to evaluate the incidence and mean survival time of cutaneous malignant melanoma (CMM) in Yazd, Iran. It seems that the epidemiology and clinical aspects of CMM in Iran are different from those in other parts of the world; also due to the limited and scattered studies there isn't lot in the lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 28 publications
3
17
0
3
Order By: Relevance
“…The least common subtypes were superficial spreading melanoma (SSM; 9%) and amelanotic melanoma (0.7%). These results were similar to those reported from Egypt, Japan, the non‐white population in Brazil and also in a study conducted in the desert climate zone of Iran; whereas the most common subtype in white populations in Australia, the USA and European countries were of the SSM type …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The least common subtypes were superficial spreading melanoma (SSM; 9%) and amelanotic melanoma (0.7%). These results were similar to those reported from Egypt, Japan, the non‐white population in Brazil and also in a study conducted in the desert climate zone of Iran; whereas the most common subtype in white populations in Australia, the USA and European countries were of the SSM type …”
Section: Discussionsupporting
confidence: 91%
“…However, recent studies from Jordan, Egypt, Turkey and Taiwan reported an overall male predominance similar to our findings . A male predominance was also reported in a study performed from 1988 to 2008 in the central part of Iran …”
Section: Discussionsupporting
confidence: 91%
“…Based on the UVR exposure map (Fig. 1A–C), Kerman (the southern province analyzed in our study) has higher erythemally-weighted average solar UVR exposure than Yazd, which may explain the higher rates of melanoma for Kerman in our study compared to those reported for Yazd in the cited reference (Noorbala et al, 2013). Another report from the population-based registry in the southern province of Fars (Fig.1A–C) found rates comparable to our study and increasing trends of melanoma for both genders.…”
Section: Discussionmentioning
confidence: 47%
“…Two previous studies, which analyzed melanoma rates using data from a single regional registry, found incidence rates compatible with ours. One study analyzed 20 years of data collected from the cancer registry of the province of Yazd in south central Iran during 1988–2008 and found the mean crude incidence rates of 0.40 per 100,000 person-years for males and 0.27 for females, with relatively fixed temporal trends (Noorbala et al, 2013). Yazd, a province with one million inhabitants, is located in the hot and dry desert area of the country with bright sunlight during most seasons.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Noorbala et al during 1988Noorbala et al during to 2008 in Yazd, a warm province in the center of Iran, the mean incidence rate for cutaneous malignant melanoma (CMM) was 0.40 per 100,000 for males and 0.27 per 100,000 for females yearly (15). Due to previously mentioned reasons, many studies have focused on Cyclooxygenase-2 (COX -2) as an inducible enzyme that is activated by UV radiation, and is a known risk factor for melanoma development (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%